Internalization Of Gender Equality Values In Family Law As An Effort To Prevent Violence Against Women - Ayang Afira Anugerahayu; Nathania Permata S; Ika Yuliana Susilawati; Ade Sultan Muhammad; I Gusti Bagus Sakah Sumaragatha; Lalu Panca Tresna; Ahwan Ahwan (Abdi Masyarakat, 2026)
Violence against women within the family remains a complex social issue in Indonesia, influenced by patriarchal culture and limited public understanding of gender equality in family law. This community service aims to internalize gender equality values through legal education in family law as a preventive effort against violence toward women. The methods used include legal counseling, participatory discussions, and community assistance in Penujak Village, Central Lombok Regency. The results indicate an increased public understanding of equal rights and obligations between spouses and greater legal awareness regarding women's protection. The implication of this activity is the formation of a more inclusive and gender-just mindset in family life. Therefore, the internalization of gender equality values can serve as a preventive strategy to reduce violence against women in society. The main output of this activity focuses on strengthening public legal literacy and establishing a collective awareness among villagers to independently prevent gender-based violence